DAMPAK KASUS PEMBAJAKAN KAPAL DI PERAIRAN SULU TERHADAP EKSPOR BATU BARA INDONESIA-FILIPINA TAHUN 2016 - Rizkia Puteri; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Indonesia is one of the largest coal exporting countries in the world and is the main source of coal importers to the Philippines as the main source of electricity generation in the Philippines. However, there are frequent hijacking of coal-laden ships in the waters of Sulu. Due to the piracy access of the Abu Sayyaf terrorism group, the national interests of the two countries were disturbed, in particular the series of kidnappings carried out by the group. Indonesia stopped sending coal exports to the Philippines at its peak in April 2016 after the kidnapping of 10 Indonesian citizens by the Abu Sayyaf Group so that the Indonesian government decided to temporarily send coal to the Philippines for a memoratorium so that the economic and political impact of the relationship between the two countries can be seen. The purpose of this study was to determine the impact of cases of ship hijacking in upstream waters on coal exports between Indonesia and the Philippines in 2016.                This research uses qualitative methods, with the level of the nation state analysis. The author uses the export theory in the perspective of neoliberalism. To analyze this case, the authors processed data from various sources of books, journals, website, official Indonesian government reports, and various relevant scientific articles to discuss the problems in this study.                Based on the results of research data analysis, it is concluded that the hijacking of coal ships from Indonesia to the Philippines in Sulu waters in 2016 had an impact on bilateral relations between Indonesia and the Philippines in the economic and political fields. The relationship between the two countries was disrupted due to the piracy case so that Indonesia postponed the shipment of coal to the Philippines until an indefinite time, therefore the Indonesian government carried out a series of cooperation in the fields of bilateral, political and maritime security to prevent and combat ship hijacking by the Group. Abu Sayyaf..Keywords: Indonesia, Filipina, Export, Coal, Impact, Taxation Case, Abu Sayyaf, Crime